Changes in electromyographic amplitudes but not latencies occur with endotracheal tube malpositioning during intraoperative monitoring for thyroid surgery: Implications for guidelines. (16th November 2016) - Barber, Samuel R.; Liddy, Whitney; Kyriazidis, Natalia; Cinquepalmi, Matteo; Lin, Brian M.; Modi, Rahul; Patricio, Stephanie; Kamani, Dipti; Belotti, Carlo; Mahamad, Sadhana; Lawson, Bradley; Randolph, Gregory W.
Abstract : Objectives/Hypothesis: During intraoperative neural monitoring (IONM) in thyroid and parathyroid surgery, endotracheal (ET) tube migration can result in a decrease in vocalis electromyographic (EMG) amplitude without a concordant latency elevation during stimulation of the recurrent laryngeal nerve (RLN). Study Design: Retrospective review. Methods: Data were reviewed retrospectively for thyroid and parathyroid surgery patients with IONM of the laryngeal nerves from January 2015 to December 2015. Recordings of vocalis EMG amplitudes and latencies with RLN stimulation were obtained with the neuromonitoring ET tube surface electrodes in optimal baseline position, with vertical displacement away from the vocalis, and with rotational change away from baseline. Results: ET tube surface electrode EMG recordings were obtained with stimulation of seven left and three right RLNs in a total of 10 patients. Mean vocalis EMG amplitudes were reduced with vertical displacement 1 and 2 cm both inferior and superior to baseline and with rotational change (45° and 90° clockwise and counterclockwise, 180°), although amplitude change with 45° clockwise and 180° rotation did not meet statistical significance. Mean EMG latency values did not change significantly from baseline with either rotation or vertical displacement of the ET tube. Conclusions: An isolated decrease in EMG amplitude without concordant latency elevation should warrant re‐evaluation of ET tube position during thyroid and parathyroid surgery and is in contrast to a combined event, with both EMG amplitude decrease and concordant latency increase, which is more suggestive of a true neuropraxic injury. Level of Evidence: 4. Laryngoscope, 127:2182–2188, 2017